Testicular Structure and Spermatogenesis in the Naked Mole-Rat Is Unique (Degenerate) and Atypical Compared to Other Mammals - van der Horst, Gerhard; Kotzé, Sanet H.; O’Riain, M. Justin; Maree, Liana (Frontiers in Cell and Developmental Biology, 2019)
The naked mole-rat (NMR) queen controls reproduction in her eusocial colony by selecting one or two males for reproduction and suppressing gametogenesis in all other males and females. Simplified, polymorphic and slow swimming spermatozoa in the NMR seem to have been shaped by a low risk of sperm competition. Our hypothesis is that this unique mammalian social organisation has had a dramatic influence on testicular features and spermatogenesis in the NMR. We studied testicular structure as well as spermatogenic cell types and its organization in breeding, subordinate and disperser males using light microscopy and transmission electron microscopy. While the basic testicular design in NMRs is similar to most Afrotheria, the Sertoli and spermatogenic cells have many atypical mammalian features. Seminiferous tubules are extended and contain large volumes of fluid while interstitial tissue cover about 50% of the testicular surface area and is mainly composed of Leydig cells. The Sertoli cell cytoplasm contains an extensive network of membranes and a variety of fluid-containing vesicles. Furthermore, Sertoli cells form numerous phagosomes that often appear as extensive accumulations of myelin. Another unusual feature of mature NMR Sertoli cells is mitotic division. The main types of spermatogonia and spermatocytes are clearly identifiable but these cells are poorly organized and the close association of many spermatids with intercellular bridges do not seem to exist. Most spermatid heads are malformed and appear to have a disorganized chromatin network, nuclear fragmentation and an ill-defined acrosome formation from almost star-like Golgi figures. Rudimentary manchette development corresponds with the occurrence of abnormal sperm morphology. The NMR testicular organization and spermiation seems to be modified to produce spermatozoa on demand in a short period of time and then use a Sertoli cell “pump” to flush the spermatozoa into short tubuli recti and simplified rete testis. Disorder in the processes of spermiogenesis and spermiation makes staging of spermatogenesis difficult; however, four main stages could be discerned in all NMR males. These numerous atypical and often simplified features of the NMR strongly suggest a state of degenerative orthogenesis that was selected for due to the absence of sperm competition.